Five new species of Aspidistra (Asparagaceae) from Guangxi, China - Lin, Chun-Rui; Lu, Zhao-Cen; Pan, Bo; Wan, Xin-Yu; Xu, Wei-Bin; Liu, Yan (Phytotaxa, 2024)
This paper continues the publication of Aspidistra species newly discovered in the flora of China. It includes five new species of Aspidistra (Asparagaceae), namely A. longjiangensis, A. erythropoecila, A. duanensis, A. yachangensis and A. polypetala, all from Guangxi, China, are described and illustrated. The morphology, ecology, phenology, distribution, conservation status and the color illustrations are provided for all five taxa.